Wir brauchen DaF - Ricci Garotti, Federica; Missaglia, Federica; Salzmann, Katharina (Linguistik Online, 2025)
Much time has passed since the European Union, through official documents such as the Maastricht Treaty and Edith Cresson’s White Paper, recommended multilingualism to its citizens – motivated by the belief that lasting peace can only be achieved through communication. The Europe “of citizens,” as Habermas envisioned it, was to be realized through multilingualism: not through an aseptic lingua franca, and even less through a hegemonic language, but through mutual understanding among the diverse cultures of the continent. Among these languages is German, which – as Dumont (1991: 15) argued – is not merely the language of a nation, but a linguistic embodiment of European tensions and identity, the quintessence de l’Europe. Today, however, we are witnessing a regression – not only in the study of German as a foreign language, but also in the broader commitment to multilingualism tout court. Yet, as Weinrich (2000: 12) remarked, “eine möglichst große Vielfalt von Sprachen dieser Welt beim Denkgeschäft [ist zu wünschen], unter ihnen auch an keinem geringeren Platz Deutsch als Denksprache”. Against this backdrop, the following contribution presents a series of essays by Germanists who have remained passionate advocates of GFL – German as a Foreign Language – and are still actively engaged in its dissemination.